Advanced control in factory automation: a survey. Issue 5 (4th March 2017) - Dotoli, Mariagrazia; Fay, Alexander; Miśkowicz, Marek; Seatzu, Carla
Abstract : This paper provides a survey of the main advanced control techniques currently adopted in factory automation. In particular, it focuses on five classes of control approaches, namely: model-based control, control based on computational intelligence, adaptive control, discrete event systems-based control and finally event-triggered and self-triggered control. A particular focus is put on the most significant and recent contributions in these areas with attention to their application in the factory automation domain. Finally, open issues, challenges and the requirements of further research efforts for each class are pointed out.